Designing contextual worksheets to measure creative thinking skills in mathematics on probability - Hilda Mahmudah; Iik Nurhikmayati; Nia Kania; Yasir Yasir (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Students' low mathematical creative thinking skills are the motivation for this study. The aim of this research is to develop context-based student worksheets (LKPD) that assess high school students' mathematical creative thinking abilities. This study uses the ADDIE development model with five stages (Analysis, Design, Development, Implementation, Evaluation), and the research is limited to the implementation stage. The subjects were Grade X students of SMAN 2 Majalengka. The instruments used included practicality questionnaires for teachers and students, validity questionnaires for media and material experts, and effectiveness tests through small-scale trials. A Likert scale was used to collect practicality and validity data, while N-gain analysis was applied to measure effectiveness. The results showed that LKPD with a contextual approach was valid, with an average material expert score of 3.17 and media expert score of 3.50. The practicality was also very good, with teacher practicality at 96.15% and student practicality at 87.26%. The average effectiveness was in the moderate category with an N-gain value of 0.38. Based on these results, it can be concluded that the developed LKPD is feasible, practical, and effective in improving students’ mathematical creative thinking skills. The contribution of this research lies in providing empirically tested, context-based LKPD that can be used as an innovative learning resource to foster mathematical creative thinking in high school students.